Physiological responses to a 6-d taper in middle-distance runners: influence of training intensity and volume - Mujika, I.; Goya, A.; Padilla, S.; Grijalba, A.; Gorostiaga, E.; Ibanez, J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: This study examined some physiological and performance responses to a 6-d taper, and the influence of training intensity and volume on these responses. Methods: After 15 wk of training, 8 well-trained male middle-distance runners were randomly assigned to either a moderate volume taper (MVT, N = 4) or a low volume taper (LVT, N = 4), consisting of either a 50% or a 75% progressive reduction in pretaper low intensity continuous training (LICT) and high intensity interval training (HIIT). Blood samples were obtained and 800-m running performance was measured before and after taper. Results: Performance was not significantly enhanced by either taper protocol (post- vs pre-taper times 124.9 ± 4.5 vs 126.1 ± 4.2 s with LVT, 126.2 ± 8.0 vs 125.7 ± 6.6 s with MVT). For the entire group of 8 subjects, red cell count, hemoglobin (Hb), mean corpuscular volume and mean corpuscular Hb concentration significantly decreased with taper, while reticulocyte count increased. Performance changes for all subjects correlated with changes in postrace peak blood lactate concentration (r = 0.87, P < 0.01). Taper LICT correlated with changes in Hb (r = 0.77), hematocrit (r = 0.81), reticulocyte count (r = 0.73), creatine kinase (r = 0.72), and total testosterone (r = -0.78), and with posttaper red cell distribution width (r = -0.75) and lymphocyte count (r = -0.82). Taper HIIT correlated nonsignificantly with changes in red cell count (r = -0.66) and total testosterone (r = 0.68). Conclusion: It is concluded that taper-induced physiological changes in trained middle-distance runners are mainly hematological, and that distinct physiological changes are elicited from LICT and HIIT during taper. Middle-distance runners can progressively reduce their usual training volume by at least 75% during a 6-d taper.